Pelatihan Self-Make Up untuk Meningkatkan Ketrampilan Masyarakat Pulungdowo - Wida Rahayuningtyas; Retno Tri Wulandari; Ika Wahyu W (Ilin Institute, 2020)
The purpose of implementing this self-make-up training is to be skilled at making up oneself for daily activities and official activities. The training activity is carried out in 2 stages, namely, (1) giving make-up material about the concepts, techniques, and tools that are used for make-up, (2) practicing daily make-up is by using simple make-up tools. The methods that are used in this service activity are lectures, demonstrations, and practices. The method is used to emphasizes the involvement of PKK women in all series of activities. The results of the self-make-up training which was attended by 29 PKK women were the improvement of the competence or skills of women in Pulungdowo Village, Tumpang District, Malang Regency, based on the results of a survey conducted via google form before training and after training, showing significant changes. Before the training, approximately 15 participants answered that they disagree with the statement that PKK women were able to do self-make-up. While for the survey results after the training activities, approximately 20 PKK women answered agreeing about the statement that make-up training activities can improve their own skills and make up for others. Then it can apply it in everyday life.